Revision of the Calceolaria tripartita s. l. species complex (Calceolariaceae) using multivariate analyses of morphological characters - Puppo, Pamela (Phytotaxa, 2014)
The morphological variation of the Calceolaria tripartita species complex was evaluated using Principal Components Analysis (PCA) of morphological characters. Fourteen quantitative characters were measured on more than 250 herbarium specimens. The results suggest the recognition of three entities based on floral characters, especially stamen morphology. The distinction between C. mandoniana, C. chelidonioides and C. tripartita s.s. is not supported. The morphological differences between the closely related C. tripartita s.s. and C. chelidonioides were also analyzed using two characters previously used to differentiate them. Finally, the morphological variation of C. tripartita s.s. throughout its geographical range and at an intra-population level was also surveyed. Even though this species is highly variable, no further subdivision is supported morphologically. A taxonomic synopsis and a key to species of the Calceolaria tripartita species complex are provided.